2018
DOI: 10.1097/gme.0000000000000990
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause and its associated factors in Canada: cross-sectional analyses from the Canadian Longitudinal Study on Aging

Abstract: These findings provide a national estimate of ANM in Canada and show the importance of lifestyle factors and health conditions in determining menopausal age. These factors might help in risk assessment, prevention and early management of chronic disease risk during the menopausal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 52 publications
11
66
1
1
Order By: Relevance
“…Increasing risk of earlier menopause has been observed among CLSA women with cardiovascular disease; although the direction of the association remains to be elucidated. 27 Premature menopause has been related to greater cardiovascular risk, 38 diabetes mellitus, 39 depression, 40 osteoporosis, and fracture risk, 41 which could contribute to the associations between premature menopause and lower gait speed found in our study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Increasing risk of earlier menopause has been observed among CLSA women with cardiovascular disease; although the direction of the association remains to be elucidated. 27 Premature menopause has been related to greater cardiovascular risk, 38 diabetes mellitus, 39 depression, 40 osteoporosis, and fracture risk, 41 which could contribute to the associations between premature menopause and lower gait speed found in our study.…”
Section: Discussionmentioning
confidence: 53%
“…42 Premature menopause could also be a marker of perinatal history, earlier social reproductive outcomes and adversities, and poor social and health conditions during adulthood. Using the CLSA, Costanian et al 27 found education to be an important social determinant of earlier menopause. Grip strength levels are related to poor social conditions in early life, including education and income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was based on the comprehensive cohort (Comprehensive Baseline Dataset, version 3.0), which includes 30,097 community-dwelling adults aged 45-85 (15,320 women, 14,777 men) who provide data in-person at one of ten data collection sites nationwide. The remainder of CLSA participants, known as the tracking cohort (n = 20,000), provide data by telephone interview and have been previously employed for studies of women's health (15) and frailty (16). The CLSA study design and methods have been previously described by Raina and colleagues (14).…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Having no partner, having a low household income and low education levels, being a current and former smoker, and having cardiovascular disease were all associated with an earlier ANM. Meanwhile, current employment, alcohol consumption, and obesity were associated with a later ANM (12) . This means other factors aside from age, genetics and hormones are associated with early or late menopause.…”
mentioning
confidence: 97%